Dampak Strategic Agility Bumdes Terhadap Keberhasilan Pengelolaan BUMDes Ditinjau Dari Absorptive Capacity dan Channel Richness Pengurus BUMDes - Fitrianti, Fitrianti; Suleman, Nurjana; Sholehah, Nur Lazimatul Hilma (Gorontalo Accounting Journal, 2023)
This research is done to identify direct and indirect connections from absorptive filters and the richness channel toward the strategic objectives and their impact on the success of management of the bumdes in wonosari district. The study USES a quantitative method. The methods of data collection used in the study are carried out through field observation, disseminating questionnaires, interviews, documentation and literature studies. As for the population in this research is the entire bumdes county boalemo with a sampling withdrawal using sampling clusters. The data analysis technique used in the research is a path analysis technique with the help of version 24 of SPSS software. The results of this study indicate that (1) absorptive indicators affect negative and significant to the strategic features bumdes in wonosari district, (2) the richness channel has a positive influence on the strategic imports bumdes in wonosari district, (3) absorptive proximity has indirectly affected no significant positive impact on the success of bumdes' management through the strategic imports on the bumdes in wonosari district, (4) the richness channel has indirectly affected the management of bumdes through the strategic imports bumdes in wonosari district, (5) the strategic imports have a positive and significant impact on the management of the bumdes in wonosari district.